2018
DOI: 10.7759/cureus.2745
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Spontaneous Pneumothorax: A Rare Complication of Osteosarcoma

Abstract: The lungs are a common site of metastatic spread of an osteosarcoma. An affiliated simultaneous bilateral spontaneous pneumothorax (SBSP) is a rare clinical sequela of this malignancy. In this case report, we present the clinical circumstances of a young teenager who presented to our clinical setting following a diagnosis of osteosarcoma. We also illustrate the postulated pathophysiology, the tools for diagnosis and a subsequent management for this rare clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 11 publications
1
19
1
Order By: Relevance
“…The incidence of pneumothorax in this study (phase I/II; 11%) is similar to that for other TKIs (3%-16%), and is consistent with the prevalence observed in patients with relapsed/refractory osteosarcoma. 17 , 25 , 30 , 32 , 33 , 34 , 35 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of pneumothorax in this study (phase I/II; 11%) is similar to that for other TKIs (3%-16%), and is consistent with the prevalence observed in patients with relapsed/refractory osteosarcoma. 17 , 25 , 30 , 32 , 33 , 34 , 35 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pneumothorax in this study (phase I/II; 11%) is similar to that for other TKIs (3%-16%), and is consistent with the prevalence observed in patients with relapsed/refractory osteosarcoma. 17,25,30,[32][33][34][35][36][37] Our study was limited by the enrollment of only one patient with RR-DTC. Therefore, no conclusions can be drawn about the activity of lenvatinib in RR-DTC.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Pneumothorax and tumor-bronchial fistula are rare complications of pulmonary metastasis of osteosarcoma. [3][4][5][13][14][15][16] There are few reports about the complication, and the etiology remains unclear. The suspected etiologies of pneumothorax are as follows: (1) rupture of tumor tissue at the lung periphery; (2) a check valve mechanism, due to intermittent bronchiolar obstruction by tumor tissue; and (3) direct metastasis to a pulmonary cystic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumothorax caused by metastasis is reported to account for <2% of all spontaneous pneumothorax cases 1,2. Recently, however, reports about patients with pneumothorax after the initiation of chemotherapy, or targeted biological agents, including antiangiogenic agents, have increased 3–5. Interiano et al3 reported a high incidence of pneumothorax in pediatric sarcoma patients who had received antiangiogenic agents.…”
mentioning
confidence: 99%
“…3 The first patient was described by De Barrin in 1937. 4 Tariq et al 15 reported a case of simultaneous bilateral spontaneous pneumothorax in a young patient with fibular osteosarcoma. Gan et al 16 described a similar case of a patient with osteosarcoma of the right mandible who developed bilateral pneumothorax.…”
Section: Discussionmentioning
confidence: 99%